Cognitive-pragmatic concept of artistic discourse (based on the language of Olga Kobylyanska) - Руснак, Юлія Манольєвна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2021)
The development of linguistics, a multidisciplinary approach to the coverage of linguistic phenomena have led to a change in the scientific paradigm – the discursive paradigm has come instead of text-centric one. In linguistics a philological discipline has been arised – discourse studies aimed at characterizing the speech communication of people in certain situations taking into account the unity of scientific approaches. The purpose of the article is to comprehend the author’s artistic discourse as a philosophical and humanitarian reality, to form a cognitive and pragmatic concept of artistic discourse. The polysemy of the term discourse makes it possible to use the concept of artistic discourse in two meanings – broad and narrow. Discourse1, or author’s discourse, is a part of cultural space where semiotic units formed according to the laws of certain genres function, in which the author’s knowledge, information, assessments, mentality as a representative of a certain sociocultural community are creatively and verbally reproduced and which have a pragmatic load. In a narrow sense discourse2 means a fragment of text (context). The cognitive aspect (knowledge, information, assessments, mentality in general) is realized in the plan of text – author, pragmatic – in the plane of text – reader, although we are aware that such a division is to some extent conditional. For effective analysis of artistic discourse in cognitive and pragmatic aspects we consider it`s necessary to enter into scientific circulation two abstract units – cognitema and pragmatema. Cognitema is a generalized unit in which a quantum of information about the world is realized (for example, thinking, color, mental state, etc.). Pragmatema is an abstract unit which has influence into the reader.